Kinetic modeling of sodium bicarbonate pre-treatment of corn stalks for increased biogas generation during anaerobic digestion: Viability and fertilizer potential - Siddique, Md. Nurul Islam; Zaied, Khalid; Mohd. Zamri, brahim; Nora'aini, Ali; Nazaitulshila, Rasit; Muhammad Syarifuddin, Yahya; Adhikary, Sajal Kumar (Asian Publication Corporation, 2024)
Sustainability in terms of the economy and the environment is severely hampered by poor waste management in the industrial sectors and a lack of renewable energy sources to meet expanding energy demands. To address this issue, the influences of sodium bicarbonate treatment on biogas generation during the anaerobic fermentation of corn stalks were analyzed. The application of sodium bicarbonate (9%, w/w) resulted in a significantly higher generation of 14692 mL biogas with a production of 223 mL/g, which was 30% higher than the untreated sample biogas generation. Surprisingly, chemical oxygen demand elimination was boosted by a factor of ten. In addition, sodium bicarbonate stabilized the pH of fermented corn stalks. The Gompertz modeling, according to the findings, had a significant correlation coefficient (> 0.995) and fit the accumulative biogas production trends well. Sludge recapture from the fermented effluent was 0.08 m3 sludge/m3 wastewater. Sodium bicarbonate added to corn stalks may increased the cumulative methane production while lowering chemical oxygen demand (COD) levels.